Immigrant Pupils' Scientific Performance: The Influence of Educational System Features of Origin and Destination Countries - Jaap Dronkers; Manon de Heus; Mark Levels (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
This paper explores the extent to which educational system features of destination and origin countries can explain differences in immigrant children's educational achievement. Using data from the 2006 PISA survey, we performed cross- classified multilevel analysis on the science performance of 9.279 15-year-old immigrant children, originating from 35 different countries, living in 16 Western countries of destination. We take into account a number of educational system characteristics of the countries of destination and origin, in order to measure the importance of differentiation, standardization, and the availability of resources. Our results show that differences in educational achievement between immigrants cannot be fully attributed to individual characteristics. Educational system characteristics of countries of destination and origin are also meaningful. At the origin level, the length of compulsory education positively influences educational performance. This is especially the case for immigrant pupils who attended education in their countries of origin. Results show that at the destination level, teacher shortage negatively affects immigrant pupil's scientific performance. Moreover, immigrant children perform less in highly stratified systems than they do in moderately differentiated or comprehensive ones. Especially immigrant children with highly educated parents perform worse in highly stratified systems.
Keywords: 330; immigration; origin; destination; educational system; educational performance; PISA